The impact of agricultural activity towards water quality in Tasik Chini - Nasihah Sakinah , Zainudin (2013)
A study on the impact of agricultural activity towards water quality in Tasik Chini was conducted at six sampling stations which were at Laut Gumum, Laut Jerangking, Laut Melai, LAut Kenawar, Laut Pulai Balai/PLKN, and Tasik Chini Resort. A total of thirteen water quality parameters were analyzed including in situ test and laboratory analysis. All the parameters were analyzed and measured according to Department of Environment Water Quality Index and National Water Quality Standard (NWQS) for Malaysia. The physical, chemical and biological variables were temperature, turbidity, total suspended solid (TSS), dissolved oxygen (DO), pH, biological oxygen demand (BUD), chemical oxygen demand, electrical conductivity (EC), ammoniacal nitrogen (NI 3 -N), nitrate (NO), phosphate (PO 3), total coliform, and Escherichia coli (E.Coli). The result show that water quality at Tasik Chini is Class II based on WQI, which means, Tasik Chini is suitable for recreational activity and body contact is allowed, however basic treatment required for water supply. Based on NWQS, electrical conductivity (EC), total suspended solid (TSS), ammoniacal nitrogen (NI 3-N), and nitrate are Class I. Parameter for turbidity, phosphate, biochemical oxygen demand (BUD), and chemical oxygen demand (COD) under Class II. pH and dissolved Oxygen under Class III. Human activities at surrounding area near Tasik Chini affected water quality there. Agricultural activity, such as palm oil plantation at Kampung Gumum, and rubber plantation at Tanjong Jerangking indeed affects water quality in Tasik Chini and if these situation continued, may have caused environmental degradation at Tasik Chini hence may lead algal bloom in lakes.